(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe normal and abnormal fetal heart rate charts in labor and the infant status of such cases. Subjects-methods: Cross-sectional description 1035 women with a gestational age of 36 weeks or more in labor receive obstetric monitoring at Nghe An Obstetrics and Pediatrics Hospital. Result: 212 cases had abnormal fetal heart rate charts, of which 19.8% of newborns had an Apgar index < 7 points. When the types of fetal heart rate decrease combined with the 0 fluctuations, the percentage of babies born with Apgar index < 7 points increased from 18.66 to 63.86 times. Cesarean section treatment had the highest rate of 63.48%. The percentage of infants with an Apgar index < 7 was lowest in the vaginal delivery group at 16.67% and the highest in the Forceps delivery group at 24.39%. Conclusions: When evaluating a fetal heart rate chart, it is necessary to comprehensively evaluate many factors in combination to be able to diagnose fetal distress and have an appropriate treatment plan.